Mobile Application for Kesusasteraan Melayu Tingkatan 4 - Ismail, Affiqul Ikhwan; Ab Ghani, Zuriani (Journal of Computing Technologies and Creative Content, 2020)
Kesusasteraan Melayu is a High School Integrated Curriculum (KBSM) for Form 4 and Form 5 subjects. The National Ideology seeks to establish a person who is mentally and spiritually harmonious, intellectually and physically, following the Education Award. This study aims to create a mobile application of the Kesusasteraan Melayu Form 4 learning course to learn it in immersive digital and enjoyable ways. This study would concentrate on a variety of features, such as a syllabus for digital design and a quiz game. This research is also intended to develop a mobile application to provide more enjoyable and insightful learning on this subject.